Virtual Reality in Construction - Solonenko, Volodymyr; Gapeev, S.M.; Zuyenok, I.І. (Видавництво НГУ, 2017)
Virtual Reality (VR) has a long history of its development, but it was popularized in 2016 with a boom of various VR-rigs (headsets, glasses, controllers). The work of VR is to create the illusion of being present in an environment that is virtual, i.e. computer generated. When transmitting information to various human senses, VR can simulate a stay in a certain environment, room or location, which allows the user to see, hear and interact with the environment through the use of a VR headset, headphones and controllers.
Keywords: Virtual Reality; віртуальна реальність